دراسة وتحليل تأثير تغيير خوارزمية تعويض التفاوت والحجم الأصغري لكتلة المدى في شجرة الأرباع على أداء الضغط التجزيئي للصور المجسمة - ساعي, مريم; صالح, السموءل; حاتم, هبة (Latakia University Journal -Engineering Sciences Series, 2018)
Stereoscopic imagining is considered to be one of the most important techniques in computer vision that aims to recreate the depth. Stereo images are one of the most famous types of 3D images. Considering the importance of stereo image compression and the advantages of the fractal image compression, this research studied the effect of changing the minimum size of the range block in quadtree on the time of the fractal compression. Where, the long-time consumed on the self-similarity search between range and domain blocks, is considered to be one of the biggest problems in fractal image compression method. This research also studied the effect of changing the disparity estimation method, between the right and the left view in stereo image, on the quality of the compression The disparity maps were obtained using four compensation methods which are exhaustive block matching , sub pixel estimation , dynamic programming and image pyramiding and were compressed using the same method used to compress the reference image. The results were evaluated using quality and efficiency objective measures and compared with the state of art stereo image compression techniques which are JPEG based on Discrete Cosine Transform DCT and JPEG2000 based on Discrete Wavelet Transform DWT and SPIHT. يشكل التصوير المجسم أحد أهم تقنيات الرؤية الحاسوبية المستخدمة لإعادة خلق انطباع العمق. وتشكل الصور المجسمة أحد أشهر أنواع الصور ثلاثية البعد التي تتألف من صورتين يمنى ويسرى مأخوذتين لنفس المشهد. ونظرا لأهمية ضغط الصور المجسمة من ناحية وللميزات الهامة التي يتمتع بها الضغط التجزيئي من ناحية أخرى. تم في هذا البحث دراسة تأثير تغيير الحجم الأصغري لكتلة المدى في شجرة الأرباع على زمن الضغط التجزيئي, حيث يعتبر الزمن الكبير لخطوة البحث عن التشابه بين كتل المدى وكتل المجال أحد أكبر المشكلات التي تعاني منها خورازمية الضغط التجزيئي. كما تمت دراسة تأثير تغيير خوارزمية تخمين التفاوت بين صورتي المشهد الأيمن والأيسر على جودة الضغط التجزيئي, حيث تم تحصيل خريطة التفاوت بأربع طرق هي طريقة مطابقة الكتل الشاملة وطريقة التخمين اعتمادا على دقة البيكسل الفرعي وطريقة البرمجة الديناميكية وطريقة هرمية الصور. قيمت النتائج بناءأ على معايير التقييم الموضوعي لجودة وكفاءة الضغط وتمت مقارنتها مع خوارزميات ضغط الصور المجسمة المعتمدة وهي JPEG المعتمد على تحويل التجب المتقطع DCT و JPEG2000 المعتمد على تحويل المويجة المتقطع DWT و SPIHT.